An Empirical Analysis of Supply Chain BPM Model Based on Blockchain and IoT Integrated System - Zhao, Ruixue (Web Information Systems and Applications, 2019)
Cross-organizational supply chain as a generic form of business process management has become a hot topic of research and application. Blockchain and IoT technology provide effective technical support for this business process model. However, the business process model design and analysis based on blockchain and IoT technology has the following problems and challenges: (1) Lack of targeted BPM model. (2) The analysis issue of the BPM model across organizational supply chains are not clear enough. This paper proposes a cross-organizational luxury supply chain BPM(Business Process Management) Model based on Internet of Things(IoT in short) and Blockchain integrated system, also gives the simulation design and simulation analyzing results of the BPM model. The simulation results show that the designed BPM model has no deadlock and is a model that can be used directly.